TEACING TENSES IN WRITING A SCIENTIFIC PAPER THROUGH PEER TEACHING METHOD FOR FINAL YEAR UNIVERSITY STUDENTS IN COVID-19 ERA - Mu'man Mu'man; Yana Yana; Yogi Iskandar (PROJECT (Professional Journal of English Education), 2021)
The ability to write a research article is one of students’ obligation that must be mastered because final year university students are always faced to the final project especially writing an article to be published in national journal as one of the requirement to pass or graduate from the campus where she/he lectures. This research aims to identify the errors of using tenses in students’ articles. This research used the method of qualitative descriptive with test – pre-test and post-test as an instrument. Pre-test was done to measure how students understand the tenses with the functions while post-test was done after the result of pre-test needed to continue to the treatment in order to have a high good writing quality. After treatment was conducted, two groups still left three errors consisting of 33 from group 1 and 44 from group 3, and three groups left two errors consisting of 46 from group 2, 29 from group 4, and 15 from group five. From the result of post-test can be decided that peer teaching method is very effective to overcome students’ problem especially in understanding or mastering the use of tense in a research article. Keywords:  Peer Teaching, Tenses, Scientific Paper